To What Extent The "Psychological Studies" Journal Applied Methodology of publishing and Assessment - Omar Alkhaleefa (University of Science and Technology, Yemen, 2010)
To What Extent The "Psychological Studies" Journal  Applied  Methodology of publishing and Assessment  The study aimed to investigate the process of refereeing of studies that have been published in "Psychological Studies Journal" in Sudan. In its conceptual and theoretical frame, the study tackled the the issue of peer review of scientific periodicals, ethics of scientific peer review, quality and style of scientific peer review, style of the American Psychological Society and the style of publication in Psychological Studies. To achieve this aim, qualititative approach and content analysis were emplyed as a method and tool, respectively. Triangulation was used for the validity of the study. The sample of the study consisted of 6 issues of "Psychological Studies Journal" that were published between the period 2002 to 2008. 40 (67.4%) of the studies were analysed and 21.6% of studies were excluded from the analysis that were published in English as well as bibliographical ones. The study showed three main trends (a) there were 30 aspects of shorcommings of publishing studies in the periodical (b) the study has identified 14 errors in the style of publication in the periodical (c) The editorial board has commited major errors in publication of their own studies. The study has been analyse in the light of 10 factors as possible causes of the shortcomings. 10 recommendations were reached as scenarios for development and refinement of the periodical as well as 10 questions for further studies.